Legal Protection for Victims of Marital Rape from the Perspective of Victimology (Study of Bantul District Court Decisions Number 126/Pid.Sus/2023/PN.Btl) - Rahma, Salsabila Fatin Maulida; Afifah, Hasna (Journal of Public Representative and Society Provision, 2024)
This study focuses on the Bantul District Court Decision Number 126/Pid.Sus/2023/PN.Btl and examines how legal protection for victims of marital rape is being implemented in Indonesia. This study demonstrates that there is still a disconnect between theory and reality, despite the fact that the new Criminal Code has strengthened the legal foundation for prosecuting those who commit marital rape. This study highlights a number of inadequacies in the realization of victims' rights, such as the absence of sufficient legal aid and the disregard for psychological healing, by employing the Doctrinal Research Method and performing a Normative Analysis—that is, by viewing a law as the norm—through a victimological approach. The study comes to the conclusion that more extensive measures are required to guarantee that victims of marital rape obtain the protection they are entitled to, including greater availability of legal services, psychological support, and mechanical assistance.